2011
DOI: 10.1002/eat.20959
|View full text |Cite
|
Sign up to set email alerts
|

Bulimia nervosa presenting as rectal purging and rectal prolapse: Case report and literature review

Abstract: Rectal prolapse, but not rectal purging (excessive finger evacuation to induce defecation), has been formally associated with eating disorders in the medical literature. We describe a young woman with bulimia nervosa and irritable bowel syndrome who used rectal purging as a method of counteracting the effects of her binge eating and who underwent two corrective surgeries for rectal prolapse in a 15-month interval. Further research into the relationship between eating disorders, rectal purging, and gastrointest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…During the process of vomiting, a deep breathing precedes the actual vomiting to protect the lungs from aspiration followed by a strong contraction of the diaphragm down with all the abdominal muscles to expel the contents of the stomach [104]. This repetitive intra-abdominal pressure in addition to constipation, pelvic floor weakness and over-exercise is considered the rationale for the relationship between BN and RP [100,105,106]. As previously mentioned, other common purging methods in bulimic patients are the laxative and enema abuse detected in 36.5% and 7.9% of patients with ED, respectively [107].…”
Section: Bulimia Nervosamentioning
confidence: 99%
“…During the process of vomiting, a deep breathing precedes the actual vomiting to protect the lungs from aspiration followed by a strong contraction of the diaphragm down with all the abdominal muscles to expel the contents of the stomach [104]. This repetitive intra-abdominal pressure in addition to constipation, pelvic floor weakness and over-exercise is considered the rationale for the relationship between BN and RP [100,105,106]. As previously mentioned, other common purging methods in bulimic patients are the laxative and enema abuse detected in 36.5% and 7.9% of patients with ED, respectively [107].…”
Section: Bulimia Nervosamentioning
confidence: 99%
“…In one study from 2013 researchers reported that it is highly probable that GI symptoms frequently reported by inpatients with EDs are representative of FGIDs defined by the Rome‐II criteria (Abraham & Kellow, 2013). Unsurprisingly, various studies reported on IBS and symptoms of IBS in AN, BN and EDNOS (Abraham & Kellow, 2011; Boyd et al., 2005; Dejong et al., 2011; Guerdjikova et al., 2012; Perkins et al., 2005; Santonicola et al., 2012; Wang et al., 2014). A few studies focused on FGID symptoms in patients with BED (Cremonini et al., 2009; Crowell et al., 1994; Javaras et al., 2008; Levy et al., 2005; Santonicola et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In 1997 Malik et al published a case series on seven patients with BN and hypothesized that chronically high intra-abdominal pressure associated with vomiting and straining, prolonged gut transit time, and constipation contributed to the rectal prolapse observed [5]. Guerdjikova and colleagues published a case history of another BN patient that experienced rectal prolapse although in this case, rectal purging (repeated finger evacuation of feces in the rectum) was suspected to be the primary contributor [6]. In 2001 Dreznik et al published a case series describing three young women with AN and rectal prolapse [7].…”
Section: Resultsmentioning
confidence: 99%